Mortality in midlife for subgroups in Germany - Peter Haan; Anna Hammerschmid; Julia Schmieder (The Journal of the Economics of Ageing, 2019)
Case and Deaton (2015) document that, since 1998, midlife mortality rates are increasing for white non-Hispanics in the US. This trend is driven by deaths from drug overdoses, suicides, and alcohol-related diseases, termed as deaths of despair, and by the subgroup of low-educated individuals. In contrast, average mortality for middle-aged men and women continued to decrease in several other high-income countries including Germany. However, average mortality rates can disguise important differences between subgroups and the phenomenon of increasing mortality rates might also be present for subpopulations in these countries. Hence, we analyze how mortality in midlife is changing for several important demographic subgroups in Germany over the 1990–2015 period with a focus on deaths of despair. Our results show a very clear pattern: We find that mortality rates declined between 1990 and 2015, with no increases in deaths of despair for any of the subgroups. Thus, our findings starkly contrast with those for the US.
Keywords: I10; I14; J11; 330; Mortality; Lifetime inequality; Causes of death; Deaths of despair; Germany